Bale Mountains forest tree demography data - Young, Nicholas E.; Romme, William H.; Evangelista, Paul; Mengistu, Tefera; Worede, Aserat (Colorado State University. Libraries, 2013)
Prism sampling data across the Bale Mountains, Ethiopia. These data are collected from four different forests: Adelle, Rira, Odo-Bulu and Demaro.
These data are in four separate files each representing one forest location (i.e., Adelle, Demaro, Odo bulu, and Rira). Each file has the basal area factor prism value (20) used to collect the data as well as the number of prism plots collected at each specific location. Each record represents an individual tree. The columns in each worksheet include Date, Plot #, Subplot, tree #, and species. Date provides the date the data were collected, Plot# list the plot name of the tree measured. Subplot is one of the five subplots associated with each plot representing C (center), N(North), W (West), S(South), and E(East). Tree # lists tree number specific to each subplot. Species lists the species name as a two letter code representing the first two letters of the scientific name (include genus and species - see below). Finally, dhb (cm) includes the diameter at breast height for each tree species in centimeters.
Natural Resource Ecology Laboratory (NREL)
Ethiopia Project
Keywords: population structure; forest tree species; Afromontane forest; Bale Mountains; Hagenia abyssinica; size-frequency distribution; systematic review; East Africa